Volume 2: Fora 2006
DOI: 10.1115/fedsm2006-98457
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D Unsteady Flow in Squirrel-Cage Centrifugal Fan and Aeroacoustic Behavior

Abstract: The objective of this paper is the study and the analysis of the complex phenomena related to the internal flow in a centrifugal fan, using Computational Fluid Dynamics (CFD) tools, completed with experimental investigation in order to validate the used numerical models. The CFD analysis concerns 2D and 3D unsteady flow. The studied phenomena are the interactions and unsteadiness induced by the motion of the rotating blades relatively to the volute and their impact on the aeroacoustic behavior of the fan. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The grid refinement has been studied and adapted to the flow morphology minimizing element distortion and to achieve required resolution in high-gradient regions. The details of this study are reported in previous papers by Younsi et al [7,8]. An example of the retained grid mesh International Journal of Rotating Machinery is shown in Figure 6.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The grid refinement has been studied and adapted to the flow morphology minimizing element distortion and to achieve required resolution in high-gradient regions. The details of this study are reported in previous papers by Younsi et al [7,8]. An example of the retained grid mesh International Journal of Rotating Machinery is shown in Figure 6.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…They accessed the information of the pressure fluctuations in some critical positions over the volute wall. Younsi et al [4,5] studied the unsteady flow in a centrifugal fan and the overall and local behavior of a centrifugal fan. Recently, large eddy simulation has been continually considered as an effective tool to study the internal flow field of centrifugal fans [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%